INDIGENOUS FOOD FORMULATIONS OF KERALA USED IN MATERNAL CARE – AN EXPLORATORY STUDY - RAMYA.R; SHILPA JOSE (International Journal of Pharma and Bio Sciences, 2014)
In Kerala, herbal food formulations are widely used in maternal care, both pre- and post-childbirth. The present study was an attempt to understand the usage and nutritive value of these food formulations thereby documenting valuable traditional knowledge. Fifty young mothers and their elderly caretakers from Kollam district of Kerala were studied and it was observed that three extensively used food formulations of herbs Morinda reticulata, Cocos nucifera inflorescence and Asparagus racemosus were rich in energy, protein, fat, calcium, and vitamin C. Dietary pattern of young mothers revealed that the dietary intake of nutrients were inadequate when compared to Recommended Dietary Allowance suggested by Indian Council of Medical Research (2010). Consumption of the indigenous, nutrient-rich food formulations bridged the gap between the deficit in intake and the recommendations. Thus these traditional foods have nutritional value in addition to the functional benefits envisaged in Ayurveda.